THE DAKWAH TRILOGY OF RHOMA IRAMA IN THE INDONESIAN DANGDUT MUSIC STAGE - Firdaus Firdaus (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This research delves into the way Rhoma Irama integrates the arts of music, religious preaching, and politics within the urgency of his religious propagation. Rhoma Irama has successfully utilized the art of music, especially in the dangdut genre, as an effective tool to convey the message of religious preaching. Through song lyrics and his performances, he has communicated messages of morality, religion, and nationalism to a wide audience. The art of music serves as a bridge connecting Rhoma Irama with his fans, enabling him to inspire and influence many people through this art. This research employs an interactive qualitative research method with a descriptive approach. The descriptive approach is utilized to examine and clarify occurring phenomena by gathering data from relevant literature studies aligned with the research focus. The collected data is subsequently analyzed using explanatory analysis techniques. This study aims to demonstrate the role of Rhoma Irama in integrating his passion for dangdut music as well as his efforts in realizing moral and religious values, thus transforming it into a pursued medium of religious propagation. The results of this study indicate that a prominent aspect of Rhoma Irama's preaching is his active involvement in efforts to disseminate the teachings of Islam to the community. Rhoma Irama emerges as a figure who plays a significant role in spreading religious, moral, and nationalistic messages in Indonesia. His contribution extends not only to the world of music but also in other forms that shape social and political order. In this ever-evolving era, the understanding of how art, preaching, and politics can mutually support each other in the urgency of proselytizing can provide valuable insights into the comprehension of religion, art, and politics in contemporary society.